(untitled) (Journal of Rangpur Medical College, 2022)
Bangladesh is an example of a highly populous, agricultural country where melioidosis may be a significantly underdiagnosed cause of infection and death. Melioidosis is caused by a highly pathogenic, soil-borne, Gram-negative bacterium, Burkholderia pseudomallei. Diabetes mellitus is the most common risk factor. Disease manifestations vary from pneumonia or localized abscess to acute septicemia or arthritis. Culture is considered the current gold- standard for diagnosis. For the intensive phase (10 to 14 days), ceftazidime or meropenem is the drug of choice. For the eradication phase (3 to 6 months), oral trimethoprim/ sulfamethoxazole is the drug of choice. Surgery (drainage of abscess) has an important role in the management of melioidosis. A 48-year-old male, health worker of an NGO, working at Cox’s Bazar presented with fever for 1 month and gradual increasing pain and swelling of the left knee for 7 days followed by cellulitis and multiple abscess formation in the left leg. B. pseudomallei isolated from blood culture and successfully treated with meropenem. J Rang Med Col. September 2022; Vol. 7, No. 2:69-72